136=Y(X*4-7)

Simple and best practice solution for 136=Y(X*4-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 136=Y(X*4-7) equation:


Simplifying
136 = Y(X * 4 + -7)

Reorder the terms for easier multiplication:
136 = Y(4X + -7)

Reorder the terms:
136 = Y(-7 + 4X)
136 = (-7 * Y + 4X * Y)

Reorder the terms:
136 = (4XY + -7Y)
136 = (4XY + -7Y)

Solving
136 = 4XY + -7Y

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-4XY' to each side of the equation.
136 + -4XY = 4XY + -4XY + -7Y

Combine like terms: 4XY + -4XY = 0
136 + -4XY = 0 + -7Y
136 + -4XY = -7Y

Add '-136' to each side of the equation.
136 + -136 + -4XY = -136 + -7Y

Combine like terms: 136 + -136 = 0
0 + -4XY = -136 + -7Y
-4XY = -136 + -7Y

Divide each side by '-4Y'.
X = 34Y-1 + 1.75

Simplifying
X = 34Y-1 + 1.75

Reorder the terms:
X = 1.75 + 34Y-1

See similar equations:

| 4y=4x+2 | | 3(5x-4)-(3x+2)=16 | | 9x=5x+56 | | 4(t-2)+6t=5(2t+2)-9 | | 2x^2+3=-6x | | 9x=5x+55 | | 15-a+5a=5 | | 3x-4x=8-3 | | -7(2x-4)+5x=5(x+6) | | (x+4)=(2x+5) | | c=10-2.5 | | (x+5)=(x-9) | | y=10-2.5 | | -6(-4u+4)-5u=3(u-4)-2 | | 15-(-47)= | | 6(x-1)=-3(2-x)+3 | | -16t^2+128t+16.25=0 | | -6(y+2)=3y-9+3(2y+5) | | -x^2+3x+8=0 | | 3+7+6=2x+5+5x | | (-b^3)(d^2)=0 | | -4(v+1)=-6v-22 | | SolveV=lwhforH | | 3u-9=17(u-3) | | (4+x)+2= | | 650=0.3536x+14.857 | | 8(v+2)=-8v+32 | | 12log(e)(x)=33 | | 5x+2+-4x=7+-19 | | 11=3(y+5)-5y | | 12ln(x)=33 | | 5(x-5)-7x=-37 |

Equations solver categories